PENGARUH METODE PEMBELAJARAN DAN KEPRIBADIAN TERHADAP KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA SMA NEGERI DI CIBINONG - Rizky Mirani Desi Pratama (LPPM Universitas Bina Sarana Informatika, 2018)
The purpose of this study was to show the influence of learning methods and personality towards English speaking skill. Sample size is 60 students consist of 30 students in experiment class and 30 students in control class and the sampling technique is intact class based on Factorial Group design. Research instrument used is a questionnaire about the personality of students who have tested its validity with the reliability coefficient of 0.875 and the test of speaking skills. Data analysis using descriptive statistical method, normality test, homogeneity test and two way ANOVA.The results showed: 1) There are significant effects of learning methods towards English Speaking skill as Fo = 85,435 and sig. = 0,000 < 0,05 2) There is a significant effect of personality towards English Speaking skill, as Fo = 6,741 and sig. = 0,012 < 0,05. 3) There is no significant effect of learning method and personlity towards English Speaking skill as Fo = 1,305 and sig. = 0,258 > 0,05. The results of this study is useful for improving the students’ English speaking skills by using suggetopedia method by considering the factor of student personality type Keywords: Learning Method, Personality, and English Speaking Skill